ETIKA PERILAKU PERGAULAN MAHASISWA KOST DI LINGKUNGAN RW 2 KELURAHAN KEBUN BUNGA KOTA BANJARMASIN - Muhrin Muhrin (Jurnal Salome : Multidisipliner Keilmuan, 2023)
Behaving ethically has a very strategic role in improving the quality of individuals in group life in a society that has its own values and norms. Individual students who mingle with the community are obliged to follow the ethical values that apply in general and specifically that apply in the community. The application of social behavior ethics can focus on ways of speaking or establishing communication, greeting each other, social reintegration, respect, politeness, and empathy. The ethics of student social behavior in RW 2 Kelurahan Kebun Bunga, Banjarmasin City, often lacks interaction and lacks politeness. Preventive efforts are made by making regulations in the RT environment and in boarding houses to comply with the rules that are made and approved.